(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Describe the characteristics of treatment compliance of elderly patients with type 2 diabetes monitored on an outpatient basis at Hanoi Heart Hospital in 2023. Subject and method: A cross-sectional study was conducted in 250 patients over 60 years old and had diagnosed with type 2 diabetes for over 6 months, who had received outpatient treatment departement at Hanoi Heart Hospital from March to August 2023. The questionnaire includes including general characteristics, clinical and treatment characteristics, adherence characteristics including 4 groups of factors (nutrition adherence, physical activity adherence, medication adherence and blood sugar control adherence). Results: The overall treatment compliance rate of patients was 14.4%. In which: The rate of compliance with blood sugar control and regular follow-up examinations was the lowest at 26.0%; Diet compliance rate was 38.8%; The rate of compliance with physical activity was 44.4% and compliance with medication was 76.0%. Conclusion: The compliance rate for type 2 diabetes treatment among elderly patients is still low. The highest compliance rate is medication use, the lowest is blood sugar control and regular followup visits.